Impacto psicosocial de la estética dental en pacientes según sexo, de dos centros de salud, Iquitos 2025 - Alva Salas, Liliana (2025)
The main objective of this research was to determine if there are significant differences in the psychosocial impact of dental aesthetics in patients, according to sex, treated in two health centers, Iquitos 2025. Opting for a quantitative, non-experimental and comparative descriptive study, a sample of 172 patients was taken and the Questionnaire on the Psychosocial Impact of Dental Aesthetics (PIDAQ) was applied. Among the results, no statistically significant relationship was found between age and the psychosocial impact of dental aesthetics, being the association very weak and positive; however, there are significant differences in the total psychosocial impact according to sex, where sex influences the overall level of impact. No significant differences were observed in the psychosocial impact between the health centers evaluated, so the perception does not vary according to the center, and when analyzing the different dimensions (dental self-confidence, social impact, psychological impact and concern for aesthetics), there were also no significant differences between sexes, although the social impact showed a trend close to significance. They concluded that the majority of participants reported low or moderate impact, with these levels predominating overall. However, women reported a higher proportion of moderate or high impact compared to men. This overall difference by sex was significant in both centers evaluated in 2025.